Analisa UI/UX pada Aplikasi Pemesanan Tiket PT. Panorama JTB Tours menggunakan Metode User Centered Design (UCD) - Nataza, Syali Oktavia; Hertyana, Hylenarti; Rahmawati, Eva (LPPM UNIKA Santo Thomas Medan, 2023)
Ticket booking applications have become one of the popular ways for tourism companies to provide convenience and comfort for customers in planning their trips. PT. Panorama JTB Tours focuses on travel services by developing a ticket booking application to improve the company's user experience and efficiency of the booking process. The author analyzes the User Interface and User Experience from the PT. Panorama JTB Tours uses the User Centered Design (UCD) method. The UCD method is used to ensure that the application design focuses on user needs, preferences and behavior. The steps of the UCD method include the stages of collecting data about users, analyzing user needs, designing UI and UX, as well as testing and evaluating designs with users. Data is collected through interviews, surveys, and observations with users. The results of the analysis provide in-depth insight into user preferences and concerns during the ticket booking process. UI and UX redesign was carried out based on findings from research, with the aim of improving navigation, layout and user interaction.